2017
DOI: 10.1016/j.jairtraman.2017.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The impact of low cost carriers on non-aeronautical revenues in airport: An empirical study of UK airports

Abstract: The purpose of this study is to clarify the impact of low cost carriers (LCCs) on non-aeronautical revenues in 26 UK airports from 1999 to 2008. Increasingly non-aeronautical revenues have become an important source for airport revenue. Our literature review highlights that there is little consensus in empirical results concerning LCC impact on non-aeronautical revenues, some of these report positive impact while others show negative impact. We estimate a non-aeronautical revenue function which includes freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Zhang and Zhang ( 20 ) investigated the optimal pricing between NAR in concession and aviation profit-making activities, and since then, the importance of NAR has been further emphasized at international airports. Many previous studies have also suggested that NAR has further increased in importance to the airport industry ( 3 , 2123 ). Graham ( 24 ) investigated the importance of NAR for today’s airports.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Zhang and Zhang ( 20 ) investigated the optimal pricing between NAR in concession and aviation profit-making activities, and since then, the importance of NAR has been further emphasized at international airports. Many previous studies have also suggested that NAR has further increased in importance to the airport industry ( 3 , 2123 ). Graham ( 24 ) investigated the importance of NAR for today’s airports.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The critical point of this discussion is how airport management can maximize an airport’s competitiveness by enabling various revenue sources. This leads each airport management to consider the effects of introducing various policies that increase aeronautical and non-aeronautical revenue ( 3 ).…”
mentioning
confidence: 99%
“…activities not directly resulting through the operation of aircraft. This encompasses revenues from commercial activities within the terminals such as food and beverage, retail, car parking and rents for terminal space and airport land (Graham, 2009;Yokomi et al, 2017).…”
Section: Airports and Non-aeronautical Revenuesmentioning
confidence: 99%
“…Together with non-aeronautical revenue it makes up total operating revenue of the airport. In general, the issues of non-aeronautical revenue get more coverage in research in terms of their determinants (Fasone, Kofler, and Scuderi, 2016) , share and structure development over time (Graham, 2009) as well as strategies used to increase it (Puls and Lentz, 2018), especially with the expansion of low cost carriers (Yokomi, Wheat, and Mizutani, 2017). At the same time, less attention is paid in research to aeronautical revenue which is often taken for granted as it is sometimes wrongly believed to only reflect the underlying cost basis.…”
Section: Introductionmentioning
confidence: 99%